Black Subjects : Identity Formation in the Contemporary Narrative of Slavery - Keizer, Arlene (Ithaca, NY : Cornell University Press, 2018)
Writers as diverse as Carolivia Herron, Charles Johnson, Paule Marshall, Toni Morrison, and Derek Walcott have addressed the history of slavery in their literary works. In this groundbreaking new book, Arlene R. Keizer contends that these writers theorize the nature and formation of the black subject and engage established theories of subjectivity in their fiction and drama by using slave characters and the condition of slavery as focal points.In this book, Keizer examines theories derived from fictional works in light of more established theories of subject formation, such as psychoanalysis, Althusserian interpellation, performance theory, and theories about the formation of postmodern subjects under late capitalism. Black Subjects shows how African American and Caribbean writers' theories of identity formation, which arise from the varieties of black experience re-imagined in fiction, force a reconsideration of the conceptual bases of established theories of subjectivity. The striking connections Keizer draws between these two bodies of theory contribute significantly to African American and Caribbean Studies, literary theory, and critical race and ethnic studies.
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- Introduction. "The Middle Passage Never Guessed Its End": New World Slavery in Contemporary Literature -- 1. Beloved: Ideologies in Conflict, Improvised Subjects -- 2. Being, Race, and Gender: Black Masculinity and Western Philosophy in Charles johnson's Works on Slavery -- 3. The Chosen Place, The Timeless People: Late Capitalism in the Black Atlantic -- 4. Performance, Identity, and "Mulatto Aesthetics" in Derek Walcott's Dream on Monkey Mountain -- 5. The Geography of the Apocalypse: Incest, Mythology, and the Fall of Washington City in Carolivia Herron's Thereafter johnnie -- Conclusion. "One Lives by Memory, Not by Truth" -- NOTES -- WORKS CITED -- INDEX
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Feb 2019).
Includes bibliographical references (pages 189-198) and index.
JSTOR
Keywords: Walcott, Derek; Walcott, Derek; Andrae, A; Walcott, Derek, -- 1930-2017.; American fiction -- 20th century -- History and criticism; Caribbean literature (English) -- History and criticism; Identity (Psychology) in literature; Slavery in literature; African Americans in literature; Slave trade in literature; Black people in literature; Roman américain -- 20e siècle -- Histoire et critique; Esclavage dans la littérature.; Littérature antillaise (anglaise) -- Histoire et critique; Identité (Psychologie) dans la littérature.; Noirs américains dans la littérature.; Traite des esclaves dans la littérature.; Personnes noires dans la littérature.; LITERARY CRITICISM / American / African-American.; Slave trade in literature; Black people in literature; African Americans in literature; American fiction; Caribbean literature (English); Identity (Psychology) in literature; Slavery in literature; USA; Roman; Letterkunde; Amerikaans; Caribisch; Slavernij; Identiteit; Herinneringen; 18.06 Anglo-American literature; 18.07 English literature outside Europe and the USA; 1900-1999; Geschichte 1980-2000.; Criticism, interpretation, etc